Desigualdades urbanas: reflexões sobre o acesso à terra e à moradia na Região Metropolitana de Belo Horizonte/MG - Hamilton Moreira Ferreira (2019)
This thesis presents the results of exploratory and descriptive research on, interrelations between the formal and informal real estate markets of the metropolitan region of Belo Horizonte/MG. The objective of this work was to expand the knowledge about social processes related to formal and informal residential markets that contributes to the emergence and maintenance of urban inequalities. It is a subject seldom investigated in urban and regional studies and on urban inequalities. Records were made about urban social inequalities, unequal access to land and housing in the Belo Horizonte metropolitan region and theoretical approaches that allow integrated readings on urban space and land and real estate markets. Precarious settlements in the Belo Horizonte metropolitan region were identified, they are considered as one of the main materializations of social inequalities in the territory. The characteristics of the formal land and real estate markets of Belo Horizonte metropolitan region and their impacts on territory and urban inequalities were investigated. Finally, to substantiate the discussions, three case studies were developed in areas considered emblematic within the Belo Horizonte metropolitan region. The results reveal a complex and heterogeneous reality. Connections, influences, proximities and isolations were identified between the formal and informal real estate markets of the surveyed localities and the need for integrative perspectives in urban investigations on social inequalities were identified.